PENGARUH KEPEMIMPINAN, KOMPETENSI DAN TEKNOLOGI INFORMASI TERHADAP AKUNTABILITAS BAGI PENGELOLA DANA DESA - Mifta Imel; Arifuddin; Erwin Hadisantoso (Jurusan Akuntansi, Universitas Halu Oleo, 2026)
This study aims to determine the influence of leadership, competence, and information technology on the accountability of village fund managers in Sawerigadi Sub-district, West Muna Regency. The sample consists of all 50 village officials in Sawerigadi Sub-district who are directly involved in village financial management, selected using a saturation sampling technique. Data collection was conducted by distributing questionnaires to respondents, with measurements based on a Likert scale. The data were processed using multiple linear regression analysis. The results indicate that leadership has a positive influence on accountability; the more effective the leadership of the village head, the higher the accountability of the village fund managers. Similarly, competence significantly enhances accountability, showing that better-qualified village officials lead to improved management standards. Finally, information technology has a positive impact, suggesting that the integration of better technological tools in financial management strengthens the accountability of village fund managers in fulfilling their responsibilities.